Pediatric face transplantation: a viable option?. Issue 5 (October 2018) - Dorante, Miguel I.; Tasigiorgos, Sotirios; Pomahac, Bohdan
Abstract : Purpose of review: Face transplantation is no longer a young field. Reported outcomes suggest that this life-enhancing transplantation is viable and ethically justified for appropriate patients. Given that pediatric hand transplantation has been performed with promising reported outcomes, it is time to consider how to properly expand the field of face transplantation into pediatric patients. Recent findings: Appropriate collaboration between adult and pediatric colleagues can mitigate risks associated with expanding surgical innovation between respective patient demographics. The reported outcomes of the first pediatric hand transplant question the appropriateness of increasing immunosuppression burden to a patient on an existing regimen for prior solid organ allotransplantion. Young donor allografts prove to be more resilient, however, implying that managing rejection episodes is key to long-term viability. Expanding face transplants into a younger population must consider the social functions of the face, and may facilitate healthy personal development given the cultural value appearance has in real life and in social media. Summary: We believe that pediatric face transplantation is not just a viable option, but an ethically reasonable one as long as the field proceeds with cautious optimism.